2020
DOI: 10.3390/ma13173724
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Behavior of Extended End-Plate Connections Subjected to Cyclic Loading on the Top-Side of the Column

Abstract: The extended end-plate connections provide excellent performance in resisting seismic loads in high-risk areas. Most scholars’ experiments and finite element studies on this type of joint are focused on the method of applying displacement loads on the beam tip, while the method of applying displacement on the column side has not been the subject of further study. However, the load transmission mechanism of this type of connection is not completely consistent in actual engineering, as the design concept of “str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The moment-rotation responses for all specimens are illustrated in Figure 4 , and the test results are provided in Table 2 . (The specimens IC-EP1/2 and EC-EP1/2 refer to previous research work [ 31 ]), and the specimen IC-EP3/EC-EP3 are newly added test data. Figure 4 a,b shows that slight differences existed between the west connection and east connection.…”
Section: Test Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The moment-rotation responses for all specimens are illustrated in Figure 4 , and the test results are provided in Table 2 . (The specimens IC-EP1/2 and EC-EP1/2 refer to previous research work [ 31 ]), and the specimen IC-EP3/EC-EP3 are newly added test data. Figure 4 a,b shows that slight differences existed between the west connection and east connection.…”
Section: Test Overviewmentioning
confidence: 99%
“… Details of joint specimens (dimensions in mm): ( a ) Detail drawing of the connection; ( b ) layout of the end-plate and bolts; ( c ) overall size of intermediate column (IC) joints [ 31 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is necessary to assess the fatigue behaviour of this type of joint, especially depending on the features that determine its operation (the lever lengths). There are numerous research papers on the behaviour of classic bolted connections [10][11][12][13][14][15][16][17], many of them focused on fatigue. For example, Zampieri et al [18] carried out a review of the fatigue resistance of bolted shear connections, Bartsch et al [19] performed an analysis of the fatigue strength of end plate connections with prestressed bolts, and Liu et al [20] showed a simplified modelling strategy based on continuous damage mechanics for the evaluation of cumulative fatigue damage in metal bolted joints.…”
Section: Introductionmentioning
confidence: 99%